The sea before us [large type] - Sundin, Sarah (Sunrise at Normandy, 2018)
In 1944, American Naval officer Lt. Wyatt Paxton arrives in London to prepare for the Allied invasion of France. He works closely with Dorothy Fairfax, who pieces together reconnaissance photographs with holiday snapshots of France -- including those of her family's summer home -- in order to create accurate maps of Normandy. As the two spend concentrated time together, in the pressure cooker of war, their deepening friendship threatens to turn into something more. But both of them have too much to lose to give into love ...